Exploring Semantic Complexity in Diplomatic Discourse: Examples of Synonyms, Antonyms, Homonyms, and Polysemy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Diplomatic discourse is characterized by a rich and nuanced vocabulary, with terms that often carry multiple meanings and interpretations. This article examines the semantic complexity of diplomatic language, focusing on examples of synonyms, antonyms, homonyms, and polysemy within the context of international relations. By exploring these linguistic phenomena, we gain insights into the intricacies of diplomatic communication and the dynamic nature of diplomatic terminology.